2014
DOI: 10.1177/1046878114549426
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Redo From the Point of Error

Abstract: Background. Training simulations provide opportunity for users to repeat actions in order to master a task. Once a mistake has been identified, however, difficulties may arise in replicating the exact sequence of previous actions, particularly in complex, open-ended environments.Technology. Alongside the advent of virtual 3D environments for learning, technology can more easily support a focus on the error in ways that were previously arduous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The difference in knowledge of sepsis gained by didactic instruction or simulation alone is unclear due to assessments obtained after the combined interventions. Previous studies [20,43] support both didactic instruction and simulation as an effective strategy to support metacognition.…”
Section: Knowledge Findingsmentioning
confidence: 93%
See 2 more Smart Citations
“…The difference in knowledge of sepsis gained by didactic instruction or simulation alone is unclear due to assessments obtained after the combined interventions. Previous studies [20,43] support both didactic instruction and simulation as an effective strategy to support metacognition.…”
Section: Knowledge Findingsmentioning
confidence: 93%
“…Results indicated that there was no transfer of decision-making capability. [19] Scoresby and Shelton [20] studied undergraduate college students' learning using 3D simulation to re-do their actions by focusing on the point of error. Results indicated that students used metacognition and reflection in varying degrees as a scaffolding mechanism to identify their failure and avoid making the same mistakes.…”
Section: Repeat/repetition Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are like other studies and suggest simulation-based education's effectiveness is related to increased reflection time. [6,29,30] The immediate repeat of the simulation resulted in two faculty facilitated debrief sessions thus creating greater support and reflection time. Second, simulation standards [11] call for educators to evaluate the effectiveness of scenarios.…”
Section: Positive Reactionsmentioning
confidence: 99%
“…[2] Airline pilots, astronauts, and the military frequently rehearse complex skills in a simulated environment to improve performance. [3][4][5] Nursing students also rehearse the execution of complex tasks in simulation; [6,7] however, only one study describes the effect of nursing students imme-diately repeating a scenario to improve performance. [8] The impact of immediate repetitive experiential practice on the affective domain of nursing students in a simulated learning environment is novel and underreported.…”
Section: Introductionmentioning
confidence: 99%